Impact of washera sheep on household income and livelihood of washera sheep producers in southern Gonder districts (Farta and Lai-gaint) - Habtemariam; Shigdaf; Agraw; Yenesew; Yeshewas; Simegnew (Global Journal of Food and Agribusiness Management, 2021)
The study was conducted at Farta and Lai-gaint districts where there is huge sheep production. However, this production was not able to give expected benefits. To alleviate this problem Andasa Livestock Research Center had conducted developmental research. The research was adapting and scalling up of washera breed sheep with other supplement research activities. Potential sheep producers (N=118 fatter) were selected with the collaboration of the woreda and community leaders. This developmental research was conducting since 1999E.C. Finally, social economical impact study was conducted using baseline and project evaluating data. Majority of the participants (86.27%) were continuing with washera sheep production. They were able to getting considerable benefits from the sector. Some of the benefits are number of washera breed sheep was increased (null to 578±4.70 sheep/household) and Farta sheep breed become decreased (12.49±10.33 to 1.76 ± 2.9 sheep/HH). The great proportion of income of the participants of the project comes from livestock sector (4141.53±3995.45 birr/year) as compared to other sources of income. From livestock sector, sheep subsector takes the greater portion (1679.25 ± 2744.52 birr/ year) in source of income. From the three breeds, pure washera breed sheep gave larger contribution (1571.76±2625.58 birr/year). Sheep production in the study districts was economical by 1007.4 birr/year with 2.07 marginal revenue. Majority of the respondents were using the money to cover their household regular costs (salt, oil, coffee, fuel...) (77.8%), cover school cost (44.4%) and purchase inputs for crop production (35.6%). Therefore, to make the sector more economical in large scale washera breed sheep should be scaled up in to similar farming system and different research support developmental work should be done in the study districts. Besides, introducing improved highland forage, adequate veterinary service and expert’s follow up are very important.